Environmental and social impacts of domestic dog waste in the UK: investigating barriers to behavioural change in dog walkers. (1st January 2014) - Lowe, Christopher N.; Williams, Karl S.; Jenkinson, Stephen; Toogood, Mark
This study sought to investigate the behaviour and attitudes of dog walkers to picking up and disposing of dog foul, with a specific focus on bagged dog waste. Two research methods were utilised. The first explores locational and social factors influencing dog walkers' behaviour in picking up and disposing of dog faeces. Dog waste audits were conducted on popular dog walking paths in Lancashire. Secondly, the results were used to deliver an online national dog walking survey. Results of the audits suggested that availability of bins, path morphology, visibility, and path location are key factors in determining the occurrence of dog faeces. In the survey a key factor influencing behaviour was the belief that clearing up after dogs is the 'right thing to do' and this was associated with an awareness of health risks. Dog walker typologies are also proposed heuristically, ranging from those dog walkers that are 'proud to pick up' who will pick up in any location, through those who make contextual judgements about where and when it could be permissible to leave dog waste, to the 'disengaged' who will not pick up even if they are aware of the health and environmental consequences. The study advocates active engagement of dog walkers in tackling this contested, potentially environmentally damaging issue.